An analysis of biomass consumption and economic growth in transition countries - Bildirici, Melike; Ozaksoy, Fulya (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
In this paper, the relationship between biomass energy consumption and economic growth was analysed for some European Transition Countries. Two econometrical methods, which are time series (Autoregressive Distributed Lag (A.R.D.L.) bounds testing approach and Granger Causality) and Panel data methods (Pedroni test, Panel Johansen test and Panel Causality test) were used to determine the cointegration relationship between the variables. A.R.D.L. and Granger Causality methods were practiced for Albania, Bulgaria and Romania for the 1981-2014 period. Panel Cointegration and Causality methods were applied for Bosnia and Herzegovina, Czech Republic, Hungary, Macedonia and Slovak Republic for the 1991-2014 period; and Croatia, Estonia, Latvia and Slovenia for the 1995-2014 period. According to the results, while short-run and long-run causality results demonstrate that the conservation hypothesis is valid for Albania and the countries in group 1, evidence of the growth hypothesis is supported for Bulgaria, Romania and the countries in group 2. In strong causality results, evidence of bidirectional causality for all countries is found.
Keywords: Biomass; transition countries; ARDL; Panel Granger causality; Pedroni test; Panel Johansen test; RENEWABLE ENERGY-CONSUMPTION; COINTEGRATION VECTORS; PANEL COINTEGRATION; NEXUS; TESTS; INFERENCE; HYPOTHESIS; MODELS; TURKEY; Business & Economics